Six Newly Sequenced Chloroplast Genomes From Trentepohliales: The Inflated Genomes, Alternative Genetic Code and Dynamic Evolution - Fang, Jiao; Liu, Benwen; Liu, Guoxiang; Verbruggen, Heroen; Zhu, Huan (Frontiers in Plant Science, 2021)
Cephaleuros is often known as an algal pathogen with 19 taxonomically valid species, some of which are responsible for red rust and algal spot diseases in vascular plants. No chloroplast genomes have yet been reported in this genus, and the limited genetic information is an obstacle to understanding the evolution of this genus. In this study, we sequenced six new Trentepohliales chloroplast genomes, including four Cephaleuros and two Trentepohlia. The chloroplast genomes of Trentepohliales are large compared to most green algae, ranging from 216 to 408 kbp. They encode between 93 and 98 genes and have a GC content of 26-36%. All new chloroplast genomes were circular-mapping and lacked a quadripartite structure, in contrast to the previously sequenced Trentepohlia odorata, which does have an inverted repeat. The duplicated trnD-GTC, petD and atpA genes in C. karstenni may be remnants of the IR region and shed light on its reduction. Chloroplast genes of Trentepohliales show elevated rates of evolution, strong rearrangement dynamics and several genes display an alternative genetic code with reassignment of the UGA/UAG codon presumably coding for arginine. Our results present the first whole chloroplast genome of the genus Cephaleuros and enrich the chloroplast genome resources of Trentepohliales.